2010
DOI: 10.1007/s00428-010-0906-8
|View full text |Cite
|
Sign up to set email alerts
|

Cystic dysplasia of the epididymis: a disorder of mesonephric differentiation associated with renal maldevelopment

Abstract: The occurrence of congenital epididymal malformations with a cystic component has not been fully characterized. Most epididymal cysts occur later in life and are likely acquired. In addition, congenital malformations of the male excretory system are extremely uncommon in fetuses and neonates, and epididymal dysplastic changes have not been reported in these cases. In this study, we report 20 cases (including 19 fetal/neonatal autopsies and one surgical specimen from an older child) showing the same spectrum of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 36 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…By 10.5 embryonic days in mice, tubules emerge from the mesonephric duct; then between 11.5 and 13.5 embryonic days, convoluted mesonephric tubules are bound to the mesonephric duct (Vuzquez et al 1998). It has been reported that slight misalignment in embryogenesis might be involved in late mesonephric duct tissue remodeling, dilated epididymal ducts, rete testis dilation, and multicystic kidneys (Smith et al 2008;Nistal et al 2010). From these findings, abnormal cellular metabolism in the MRL strain might affect tissue organization from mesenchymal origin and the differentiation of the mesonephric duct in embryogenesis.…”
Section: Possible Primary Causes Of Ovarian Cysts In Mrl Micementioning
confidence: 99%
“…By 10.5 embryonic days in mice, tubules emerge from the mesonephric duct; then between 11.5 and 13.5 embryonic days, convoluted mesonephric tubules are bound to the mesonephric duct (Vuzquez et al 1998). It has been reported that slight misalignment in embryogenesis might be involved in late mesonephric duct tissue remodeling, dilated epididymal ducts, rete testis dilation, and multicystic kidneys (Smith et al 2008;Nistal et al 2010). From these findings, abnormal cellular metabolism in the MRL strain might affect tissue organization from mesenchymal origin and the differentiation of the mesonephric duct in embryogenesis.…”
Section: Possible Primary Causes Of Ovarian Cysts In Mrl Micementioning
confidence: 99%
“…Congenital seminal vesicle cyst or Zinner syndrome is a rare disease of the genital system, which may be associated with other abnormalities of the reproductive system or urinary system, such as Mullerian duct cysts, ipsilateral vas deferens agenesis, abnormity of the upper urinary tract, ureterocele, or ureter agenesis, hypospadias, and abnormality of the testes, epididymis and adrenal glands (Casey, Stunell, Buckley, Flynn, & Torreggiani, ; Das & Amar, ; Fujita, Goto, & Saiki, ; Hihara et al, ; Kenney & Leeson, ; Khanduri et al, ; Manousakas et al, ; McGee, Hutcheson, Vandersteen, Reinberg, & Wolpert, ; Naval‐Baudin et al, ; Nistal et al, ; Ornstein & Kershaw, ; Patel, Gujral, Jefferson, Evans, & Persad, ; Sandler, Newhouse, & Dunnick, ; Shariat, Naderi, Miles, & Slawin, ; van den Ouden et al, ). Table presents a detailed list of these abnormalities.…”
Section: Resultsmentioning
confidence: 99%
“…The larger the cyst, the earlier and obvious the symptoms present. Seminal vesicle cysts that are <5 cm stay asymptomatic and are later discovered as a palpable abdominal mass arising from the superior aspect of the prostate gland, while cysts larger than 5 cm stay symptomatic and are caused by the mass‐effect compression of the bladder or rectum (Altobelli et al, ; Aswani et al, ; Casey et al, ; Das & Amar, ; Fujita et al, ; Hihara et al, ; Hong et al, ; Kanavaki, Vidal, Merlini, & Hanquinet, ; Kenney & Leeson, ; Manousakas et al, ; McGee et al, ; Naval‐Baudin et al, ; Nistal et al, ; Ornstein & Kershaw, ; van den Ouden et al, ; Patel et al, ; Sandler et al, ; Shariat et al, ; Slaoui et al, ). Zinner syndrome can be initially determined through imaging examination after ultrasound, CT and MRI scans.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of Pkhd1 expression in the male reproductive tract is not known. However, epididymal cysts are seen in males with germline mutations of HNF-1␤ and have also been described in some patients with ARPKD, although they are not a typical feature (28).…”
Section: Discussionmentioning
confidence: 97%